High rates of same-sex attraction/gender nonconformity in the offspring of mothers with thyroid dysfunction during pregnancy: proposal of prenatal thyroid model - SABUNCUOĞLU, OSMAN TALAT (PAGEPRESS PUBL, 2015)
Both youngsters and adults with same-sex attraction are at greater risk for negative health outcomes. Despite mounting efforts to determine the biological background, a satisfactory conclusion has not been reached and there is a need to explore alternate factors like functioning of thyroid system during pregnancy. A retrospective chart review was undertaken of 790 eligible children and adolescents who had been admitted to child psychiatry between 2005 and 2013. This population consisted of 520 (65%) males and 270 (35%) females, aged 8 to 17 years. Fifteen mothers (1.8%) were found to have a history of thyroid dysfunction during pregnancy. Sixteen youngsters (2%) had a history of same-sex attraction. Twelve overlapping cases with both same-sex attraction and maternal thyroid dysfunction during pregnancy were identified, which was extremely significant (P<0.0001, by Fisher's exact test). The association was also significant for each sex (P<0.0001, by Fisher's exact test). There is evidence that thyroid gland plays a crucial and decisive role in determining sexual orientation in people. Maternal thyroid dysfunctions during pregnancy may result in homosexual orientation in the off-spring.
Keywords: Sexual orientation; homosexuality; thyroid diseases; prenatal exposure delayed effect; adolescents; ORIENTATION; DISORDERS; HORMONE